2017
DOI: 10.1158/1055-9965.epi-16-0508
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin Use and Reduced Risk of Pancreatic Cancer

Abstract: Background Few options beside avoidance of smoking and obesity are available to prevent pancreatic cancer. The association between aspirin use and risk of pancreatic cancer has been inconsistent across studies. Methods We performed a population-based study of 761 case and 794 control subjects frequency matched on sex and age during 2006–2011 in Shanghai, China. Participants were asked about episodes of regular use of aspirin, tablets per day or week, and ages that use started and stopped. Data were analyzed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
52
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 24 publications
2
52
1
1
Order By: Relevance
“…Brasky and Wactawski-Wende note that in Figures 1 and 2 of our paper (1), the years shown with the individual studies do not correspond to the publication years of the papers. This observation is correct; the years are the approximate midpoints of the periods of case collection in each of the studies.…”
mentioning
confidence: 60%
See 2 more Smart Citations
“…Brasky and Wactawski-Wende note that in Figures 1 and 2 of our paper (1), the years shown with the individual studies do not correspond to the publication years of the papers. This observation is correct; the years are the approximate midpoints of the periods of case collection in each of the studies.…”
mentioning
confidence: 60%
“…The second study showed that low-dose aspirin inhibits platelet c-MYC regulation and PANC-1 cancer-cell proliferation (4). If these findings are confirmed, they would provide possible mechanisms for the reduced risk of pancreatic cancer that has been increasingly seen in studies of aspirin use (1). …”
mentioning
confidence: 85%
See 1 more Smart Citation
“…That work suggests that aspirin use may slow the growth of such cysts. If this finding is substantiated, it would provide a mechanism underlying the reduced risk of pancreatic cancer that has been increasingly observed in studies of aspirin use (1). …”
mentioning
confidence: 86%
“…I thank Dr. Mormile for her suggestion that our observed reduced risk of pancreatic cancer with aspirin use (1) might arise from down regulation of the anti-apoptosis protein survivin (2). Survivin has been observed to be expressed by cancer tissue but not normal tissue (3).…”
mentioning
confidence: 99%